The Effect of Exercise Intervention on Improving Sexual Performance in Primiparous Women - Aldiyar E. Masalov; Ali Abdulhussain Fadhil; Husam Abdulkadhim Raheema; Farah A. Dawood; Abdul Razzaq Jabr Al Majidi; Sarmd D. Noori; Ahmed Y. Saleh; Daniyar S. Bokin (Mashhad University of Medical Sciences, 2024)
Background: Sexual dysfunction and incontinence are of the most crucial health concerns in the postpartum period, especially in the case of normal childbirth. Exercise interventions can be effective to reduce the aforementioned disorders.Aim: The present study was performed with aim to investigate the effect of exercise intervention on sexual performance in primiparous women.Method: This prospective clinical trial study was performed on 176 women referred to Basra Children's Hospital in 2021. The subjects were randomly assigned to test and control groups. The control group received no intervention, while the test group received physical therapy and pelvic floor exercises for ten sessions. The intervention began in the tenth week after delivery. The pre-and post-test phases were evaluated 10 and 20 weeks after childbirth. The subjects were requested to complete the prolapse/urinary incontinence sexual questionnaire (PISQ-12and the pelvic floor distress inventory short form (PFDI-20).Results: The pre-test and post-test levels of sexual performance in the test group were 33.47±3.62 and 37.16±3.93, respectively (p<0.001). In addition, the pre-test and post-test levels of pelvic floor irritation in the test group were 10.23±0.74 and 6.52±0.61, respectively (p<0.001); while, this difference was insignificant in the control group (p>0.05). Also, the sexual performance and pelvic floor irritation values in the post-test phase significantly differ between the two groups (p<0.001).Implications for Practice: In terms of enhancing sexual performance and reducing pelvic floor irritation, the impact of pelvic floor exercise was superior to routine postpartum recommendations.